Habitação sustentável - SANTOS, Edivando Domingos dos; ANDRADE, Gabriel de Paula Domingos; FERNANDES, Sandro de Almeida; OLIVEIRA, Leandro Rafael de (194, 2024)
O estudo foca em melhorias e redução do impacto ambiental na construção civil, em especial no bairro Santa Maria em Santos-SP. O projeto inserido em área de adensamento sustentável, com objetivo de desenvolver moradia que incentive o uso eficiente de recursos e promovam um estilo de vida mais sustentável, respeitando as necessidades ecológicas da região. Bem diferente das técnicas construtivas tradicionais,

This study focuses on improvements and reduction of environmental impact in Santa Maria neighborhood in Santos-SP. The project is located in an area of sustainable densification, aiming to promote a denser and more sustainable urban occupation, using urban land in an intelligent way to accommodate the population without sacrificing quality of life or the environment. The objective is to develop housing that encourages the efficient use of resources and promoting a more sustainable lifestyle, respecting the ecological needs of the region. Very different from traditional construction techniques, such as brick and concrete, the proposal of this study is to develop a construction system in galvanized steel frames, making the process faster, cleaner and more sustainable.
Trabalho de Conclusão de Curso apresentado como requisito para obtenção de Diploma Técnico em Edificações da ETEC Doutora Ruth Cardoso.
Keywords: Sustentabilidade; Construção civil; Infraestrutura